PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN MOTIVASI BELAJAR PAI PADA SISWA KELAS IX D DI SMPN 9 KRUI TP. 2022/2023 - Rahmawati (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2023)
Classroom Action Research conducted by Rahmawati with the title Application of the Problem Based Learning model to increase motivation to learn PAI in Grade IX D Students at SMPN 9 Krui TP. 2022/2023 is one of the tasks in Teacher Professional Education (PPG) in the Position of LPTK UIN Sjech M. Djamil Djambek Bukittinggi in 2022. In the teaching and learning process, motivation plays a very big role in learning achievement. Because the existence of motivation can foster student learning interest. In Islamic Religious Education learning activities that are fun must be supported by learning tools that can attract interest in learning. The problem in this study is the condition of students during the learning process of Islamic Religious Education does not occur reciprocal interaction. The research subjects were Class IX D students in the 2022/2023 academic year in PAI learning with the Material of Achieving Success with Optimism, Endeavor and Tawakkal. There were 21 students consisting of 8 male students and 13 female students. Classroom action research was carried out in three cycles, each cycle consisting of one meeting. In this study there are four stages, namely planning, implementation, observation and reflection. Data collection was carried out using observation and questionnaires. Based on the research conducted, some Pre-Cycle Learning Motivation Conditions are still low. Students who have low learning motivation are 17 students and 4 students in the medium category. The results of the observation questionnaire on student learning motivation showed that the highest score was 68.75, the lowest score was 34.37 and the average score was 55.76. After calculating the average of 21 data shows that class IX D students have a level of learning motivation that is included in the low category. After the action was taken using the Problem Based Learning (PBL) learning model in cycle I, the score became 63.13 indicating a moderate level. Student motivation increased by 9.37. Whereas in cycle II students' learning motivation obtained a score of 77.52 indicating a high level. In the third cycle, students' learning motivation obtained a score of 88.09 indicating a high level. From this presentation, when viewed from cycles I, II, and III, student motivation using the Problem Based Learning (PBL) learning model has increased.